Influência do óxido nítrico na infecção experimental por Ascaris suum durante a fase inicial da ascaridíase - Caroline Cavalcanti da Silva (2014)
Ascariasis is the most common geohelminth infection worldwide. The biological aspects related to ascariasis are remain unclear, as well as immunological and histopathological mechanisms, especially during the early phase of infection. Several studies have shown that nitric oxide is involved as a mediator in other parasitic infections and also affects the survival of the parasites in the host. Thus, the goal of this work was to study the influence of nitric oxide during the early stage of infection by Ascaris suum, by in vitro production of nitrite using the Griess reagent and cell viability by MTT assay in C57BL/6 cells stimulated by excreted/secreted antigens of A. suum larvae. Inhibitors of nitric oxide synthase (NOS), Nomega- nitro-L-arginine (LNMMA) and L-N6- (1-iminoethyl) lysine (LNIL) were used. Furthermore, we compared the parasitic load of C57BL/6 mice and animals deficient for inducible nitric oxide synthase (iNOS-/-), during migration of larvae of A. suum in the liver and lung. Histopathological and haematological procedures were also evaluated, as well as, the profile of serum cytokines and activity of eosinophil peroxidase (EPO) and neutrophils myeloperoxidase (MPO). The data showed a nitric oxide production in mouse cells stimulated by excreted/secreted antigens of A. suum larvae and these cells restored viability when inhibitors of NOS were used. During the experimental infection, higher number of larvae in the liver of iNOS-/- were found as compared to C57BL/6 (p <0.0001). In the histopathological analyses larger area of injury in the lung and reduced area of inflammatory infiltration were observed in the liver of iNOS-/- compared to wild type mice. In iNOS-/- mice we observed an absence in the modulation mediated of cytokines such as TNF- and IFN- acting in the early phase of infection, that might contribute to the failure or delay to eliminate the parasite. In the same animals, the hematopoiesis was affected and observed by the reduction in the number of erythrocytes and a substantial increase in the number of platelets. The formation of granulomas was observed only in animals iNOS-/-. In conclusion to the presented results, we showed that production of nitric oxide affects parasite migration and is involved in the immune response against A. suum.